2018
DOI: 10.1371/journal.pone.0194853
|View full text |Cite
|
Sign up to set email alerts
|

Changes in trunk posture and muscle responses in standing during pregnancy and postpartum

Abstract: The aim of this study was to analyze the position of the lumbopelvic region and the muscle activation of erector spinae and biceps femoris muscles in a group of pregnant women in the third trimester. The hypothesis was that pregnancy-related biomechanical and morphological changes modify the position of the lumbopelvic region and the activation of extensor muscles. The position of the lumbar spine and pelvis in the sagittal plane, and the EMG activity of the erector spinae and biceps femoris muscles, were reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 34 publications
2
20
0
6
Order By: Relevance
“…Así como Biviá-Roig et al (2018), Krkeljas (2018) también concuerda en mencionar que esta disparidad de resultados está fundamentada en la falta de unificación de técnicas de medición y que por lo tanto no permite establecer cambios fijos y congruentes entre sí; a pesar de que en su mayoría los autores concuerdan en sus hallazgos. Wong y McGregor (2018) concuerdan en exponer que la amplitud de definiciones de parámetros tales como ancho de paso o largo de zancada, la multiplicidad de métodos de evaluación y medición, la diferenciación de grupos de valoración, así como de la utilización de controles o mismas etapas gestacionales como referencia pueden influir en la significancia de los datos a obtener, y por lo tanto la congruencia de estos.…”
Section: Discussionunclassified
“…Así como Biviá-Roig et al (2018), Krkeljas (2018) también concuerda en mencionar que esta disparidad de resultados está fundamentada en la falta de unificación de técnicas de medición y que por lo tanto no permite establecer cambios fijos y congruentes entre sí; a pesar de que en su mayoría los autores concuerdan en sus hallazgos. Wong y McGregor (2018) concuerdan en exponer que la amplitud de definiciones de parámetros tales como ancho de paso o largo de zancada, la multiplicidad de métodos de evaluación y medición, la diferenciación de grupos de valoración, así como de la utilización de controles o mismas etapas gestacionales como referencia pueden influir en la significancia de los datos a obtener, y por lo tanto la congruencia de estos.…”
Section: Discussionunclassified
“…Other authors have used the non-resisted Biering-Sorensen test to normalize the EMG activity of the erector spinae in pregnant women (Biviá-Roig, Lisón & Sánchez-Zuriaga, 2018; Biviá-Roig, Lisón & Sánchez-Zuriaga, 2019). In this case, the task being studied was muscle activation while standing (Biviá-Roig, Lisón & Sánchez-Zuriaga, 2018) and during trunk flexion-extension (Biviá-Roig, Lisón & Sánchez-Zuriaga, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have used the non-resisted Biering-Sorensen test to normalize the EMG activity of the erector spinae in pregnant women (Biviá-Roig, Lisón & Sánchez-Zuriaga, 2018; Biviá-Roig, Lisón & Sánchez-Zuriaga, 2019). In this case, the task being studied was muscle activation while standing (Biviá-Roig, Lisón & Sánchez-Zuriaga, 2018) and during trunk flexion-extension (Biviá-Roig, Lisón & Sánchez-Zuriaga, 2019). Given that submaximal maneuvers are designed for use by patients with pain, to avoid injury, and to generate sufficient activation to normalize a wide variety of static and dynamic tasks, we propose using the Biering-Sorensen test without resistance as a submaximal reference test to normalize the erector spinae, more so when the Biering-Sorensen test has been shown repeatedly as a safe maneuver to use in patients with low back pain (Dolan et al, 2000; Conway et al, 2016)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal morphology changes from the second trimester, with the increasing size of the uterus and weight of the fetus, and there is a 30% increase in abdominal mass (4). The increase in abdomen size is related to decrease in static stability (5) and adaptive changes occurring in spinal curvatures which would compensate the anterior displacement of the center of gravity to maintain postural balance (6). It has been reported that gestational weight gain and the asymmetrical distribution of weight mainly in the anterior abdominal region (4), the adaptive postural changes necessary for readjustment of anterior-posterior center of gravity location (7), and increased joint laxity (8) may lead to changes in the static stability of a pregnant woman (5).…”
Section: Introductionmentioning
confidence: 99%